The effects of aspirin and ticagrelor on Toll-like receptor (TLR)-mediated platelet activation: results of a randomized, cross-over trial. (4th July 2019) - Hally, Kathryn E; La Flamme, Anne C; Harding, Scott A; Larsen, Peter D
Abstract: Platelet activation underlies the pathology of an acute myocardial infarction (AMI), and dual antiplatelet therapy (DAPT) is administered post-AMI to limit this activation. Platelets express Toll-like receptors (TLRs) 1, 2, and 4 and become potently activated in response to TLR2/1 and TLR4 stimulation. However, it is unknown whether antiplatelet agents can protect against platelet activation via these TLR pathways. This study aimed to determine the extent to which TLR-mediated platelet activation can be inhibited by currently used antiplatelet agents. Ten healthy subjects were enrolled into a single-blinded randomized cross-over trial. Subjects received either aspirin monotherapy or DAPT (aspirin in combination with ticagrelor) for 1 week, were washed out, and crossed over to the other drug regimen. Platelet activation was assessed in response to Pam3CSK4 (a TLR2/1 agonist) and lipopolysaccharide (LPS; a TLR4 agonist) at baseline and after each antiplatelet drug regimen. Platelet-surface expression of CD62p and PAC1 by flow cytometry was measured as markers of platelet activation. At baseline, expression of CD62p and PAC1 increased significantly in response to high-dose LPS and in a dose-dependent manner in response to Pam3CSK4. Aspirin monotherapy did not inhibit platelet activation in response to any TLR agonist tested. DAPT with aspirin and ticagrelor only modestly inhibited expression of both activation markers in response to high doses of Pam3CSK4 and LPS. However, incubation with these TLR agonists led to substantial platelet activation despite treatment with these anti-platelet agents. Platelet-TLR2/1 and platelet-TLR4 represent intact on-treatment platelet activation pathways, which may contribute to on-going platelet activation post-AMI.